AB0497 Six cases of macrophage activation syndrome as presenting manifestation of systemic lupus erythematosus. (15th June 2017) - Dall'ara, F; Cavazzana, I; Frassi, M; Taraborelli, M; Fredi, M; Franceschini, F; Andreoli, L; Tincani, A; Airò, P
Abstract : Background: Macrophage Activation Syndrome (MAS) is a life-threatening syndrome characterized by excessive immune activation. It can be triggered by conditions affecting immune homeostasis, such as infections, malignancies and rheumatologic disorders, including Systemic Lupus Erythematosus (SLE). In previous studies, prevalence of MAS among SLE patients ranged from 0.9% to 4.6%. Objectives: To describe the presentation and treatment of both MAS and SLE in patients with both syndromes. Methods: Monocentric retrospective evaluation: patients with MAS according to HLH classification criteria were identified in our cohort of SLE patients (classified according to ACR and SLICC criteria)followed for at least 1 year between 1972 and 2014. Results: Among 511 patients with SLE (mean age at diagnosis:31 years ±2), 6 patients (1.2%)with MAS were identified (all female). Their main clinical and laboratory features are reported in table 1 .Median HLH score was 226.5 (IQR 204–254), with a probability of having MAS of 96%.In all cases MAS happened simultaneously to the onset of SLE.Median age at diagnosis was 31.5 years, median SLEDAI was 12.All patients had fever above 38°C, lymphadenopathy, hematological involvement, and high titer ANA positivity. Workup for infections and malignancies was negative in all cases.All patients were treated with corticosteroids (100% received intravenous immunoglobulin pulse of methylprednisolone);concomitant medications were: cyclosporin A in 83%, IVIG in 67%, granulocyte colony-stimulating factor in 17%, mycophenolate mofetil in 17%, etoposide in 17% and plasma exchange in 17%. Two patients required haemotransfusion.All cases required hospital admission, and 2 were admitted in intensive care unit. No death from MAS was observed (median follow up: 34.5 months;IQR25–48).One patient died 44 months after after MAS for pulmonary adenocarcinoma.Table 1 :main clinical and laboratory features at diagnosis of SLE and MAS Conclusions: MAS is a rare complication in our SLE cohort and can complicate the onset of SLE, but it seems to be a very uncommon manifestation during the course of the disease.Fever may be a red flag for possible MAS, particularly if temperature is persistently above 38° in absence of signs and symptoms of underlying infection.In our series, all cases were treated successfully with immunosuppressive drugs and cytotoxic agents such as etoposide were used only in one case. Disclosure of Interest: None declared